Doppler Ultrasonographic Study on Haemodynamic Alterations in Medically Terminated Canine Pregnancies - Patruni, Sri Charan; Konjeti, Anusha; Murakonda, Mutha Rao; Mulinti, Raghunath; Ahmed, Nasreen (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study evaluated maternal and fetal haemodynamic changes in medically terminated canine pregnancies using Doppler  ultrasonography. Twelve pregnant bitches (35-40 days gestation) were divided into a Group I (control group, n=6) and Group II (treatment  group n=6). A combination protocol of cloprostenol (1 µg/kg SC every 48 h) and cabergoline (5 µg/kg PO daily) was used to induce  abortion for bitches in group II. Parameters assessed included biparietal diameter (BPD), combined thickness of uterus and placenta  (CTUP), fetal heart rate (FHR), progesterone levels, and Doppler parameters (PSV, EDV, RI, PI, S/D ratio) in the uteroplacental artery (UPA),  umbilical artery (Uma) and fetal aorta (FA). All group II bitches aborted within 3-5 days, with progesterone dropping below 1 ng/mL  by day 5. Significant haemodynamic disruptions were observed post-treatment, including increased UPA resistance (RI >0.61, EDV
Keywords: Canine pregnancy; Doppler; Progesterone; Resistive index; Umbilical artery